Advances in the Treatment of Post-cholecystectomy Diarrhoea based on Changes in Intestinal Flora - Ma, Chengyan; Gao, Yizhuo; Chen, Lingyan; Yu, Tao (Journal of Contemporary Medical Practice, 2024)
Post cholecystectomy diarrhoea (PCD) is one of the common complications after cholecystectomy, which is characterised by urgency of defecation, increased frequency of defecation, and often during the day. Although its pathogenesis is complex, after cholecystectomy, the diversity and abundance of bacterial flora are significantly altered, and intestinal microecological imbalance plays a major role in the pathogenesis of PCD, and the regulation of intestinal flora is an important means of treatment in the treatment of PCD. In this paper, we review the research progress of PCD treatment based on the alteration of intestinal flora.